Influência do Simples Nacional no quociente do valor adicionado das ME e EPP, utilizando dados do Estado do Ceará: análise dos anos 2013 a 2016 - Freire Júnior, Hamilton Monteiro (2017)
This study tries to verify the influence of "Simples Nacional" (SN) - a Brazilian simplified national tax payment system, on the quotient QVA (Value Added Quotient), which is the difference between Outputs (O) and Inputs (I) divided by Inputs, i.e. (O-I/I), on Microenterprises (ME) and Small Enterprises (EPP) in the State of Ceará. Taxpayers informations was aggregated by the All Sectors, Retail and Wholesale Trade and Industry segments for the period from 2013 to 2016. This natural public finance experiment was estimated by Descriptive Results of the Average Quotient and by econometric model of Difference of Differences, whose data were subdivided between two Groups: Control and Treatment. In the Control Group, there are those companies that did not opt for SN during the whole period: 2013 to 2016. In the Treatment Group, companies that in the years 2013 and 2014 did not opt for SN, but in 2015 and 2016 adopted to SN. The analysis of the data suggests that the level of aggregation to the values of the Inputs obtained by the quotients of the companies opting for the SN, vary according to the segment to which they belong and present smaller ones in relation to the companies that did not adopted the SN. In the light of the foregoing, in parallel, these QVAs reflect the contribution of the public policy of Simples Nacional in the tax collection performance of these companies and the confrontation between the Treatment and Control Groups.